2022
DOI: 10.1111/jam.15448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of functional diets on intestinal microbiota and resistance to Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease (AHPND) of Pacific white shrimp (Penaeus vannamei)

Abstract: Aims:The present study evaluated the effect of four functional diets and a reference diet on the survival and intestinal bacterial community of shrimp Penaeus vannamei infected with acute hepatopancreatic necrosis disease (AHPND).Methods and Results: After 42 days of feeding trail, shrimp were inoculated with a Vibrio parahaemolyticus (CIB-0018-3) carrying the plasmid encoding for the PirAB toxins responsible for AHPND. After 120 h postinfection (hpi), shrimp fed with a diet containing 2% of a mix with Curcuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…Diet F, however, needs to be administered for at least 5 weeks to improve shrimp survival after bacterial challenge. Our results are in line with those recently reported by Quiroz-Guzmán et al [ 39 ], who observed that after 6 weeks of feeding with functional diets containing curcuma and maca or vitamin C, shrimps showed significantly higher survival rates (85%) after bacterial challenge compared to that of the control groups (50%–55%). The strength of our results rests on the shorter feeding schedule with functional diet E (4 weeks vs. 6 weeks in the Quiroz-Guzmán study [ 39 ]), providing similar protective effect against AHPND.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Diet F, however, needs to be administered for at least 5 weeks to improve shrimp survival after bacterial challenge. Our results are in line with those recently reported by Quiroz-Guzmán et al [ 39 ], who observed that after 6 weeks of feeding with functional diets containing curcuma and maca or vitamin C, shrimps showed significantly higher survival rates (85%) after bacterial challenge compared to that of the control groups (50%–55%). The strength of our results rests on the shorter feeding schedule with functional diet E (4 weeks vs. 6 weeks in the Quiroz-Guzmán study [ 39 ]), providing similar protective effect against AHPND.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with those recently reported by Quiroz-Guzmán et al [ 39 ], who observed that after 6 weeks of feeding with functional diets containing curcuma and maca or vitamin C, shrimps showed significantly higher survival rates (85%) after bacterial challenge compared to that of the control groups (50%–55%). The strength of our results rests on the shorter feeding schedule with functional diet E (4 weeks vs. 6 weeks in the Quiroz-Guzmán study [ 39 ]), providing similar protective effect against AHPND. The drop of the shrimp survival after the 5-week feeding schedule compared to the 4-week schedule could indicate that animals were more vulnerable at that time for unknown reasons that might be investigated in future studies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations